Comparison of cycloplegic effects of Cyclopentolate and Tropicamide in children (2021)
In this article, a bibliographic review of the comparison of the ocular medication: Cyclopentolate and Tropicamide was carried out, with the aim of determining the cycloplegic effect in children in a poblation between 6 months and 15 years. Currently there is no specific consensus that determines which of the two drugs mentioned above is better, for this reason, the need to implement and promote new studies on this subject was raised. Methodology: bibliographic review in databases: PubMed, Medline, Scopus, Scielo, Acces Medicine, Mc Graw-Hill, where 3 variables are analyzed; Cycloplegic capacity of tropicamide and cyclopentolate in patients aged 6 months to 15 years, reaction time and recovery time of each drug, and adverse effects. Results and Discussion: the Diopter difference does not vary between the drugs, being between 0.50 D and 0.75 D, for concentrations of 0.5% and 1%, in the case of Tropicamide and Cyclopentolate, respectively.